ENDOTHELIAL DYSFUNCTION OF PERIODONTAL VASCULATURE OF GENERALIZED PERIODONTITIS - Riznyk, Світлана; Riznyk, Юрій; Pyndus, Тетяна; Pyndus, Володимир (Actual Problems of Medicine and Pharmacy, 2022)
The development of the pathological process in patient with generalized periodontitis accompanied by increased levels of ET-1 and proinflammatory cytokines such as TNF – α, IL – 1β, IL – 6 in oral fluid, which are the markers of endothelial dysfunction and contribute to the progression of inflammatory-dystrophic process in the periodontal tissues. The mechanism of the pathogenetic correlations justifies a scientific approach to the selection and usage of immunological research methods in patients with generalized periodontitis. All this testifies to a significant violation of hemodynamics of periodontal disease. Structural changes of blood capillaries with intravascular are revealed blood clotting is the basis for the appointment of such patients with prophylactic and curative anticoagulants.